Biocementation of Pyrite Tailings Using Microbially Induced Calcite Carbonate Precipitation - Bo Kang; Fusheng Zha; Weihao Deng; Runkai Wang; Xianguo Sun; Zhitang Lu (Molecules, 2022)
Tailing sand contains a large number of heavy metals and sulfides that are prone to forming acid mine drainage (AMD), which pollutes the surrounding surface environment and groundwater resources and damages the ecological environment. Microbially induced calcium carbonate precipitation (MICP) technology can biocement heavy metals and sulfides in tailing sand and prevent pollution via source control. In this study, through an unconfined compressive strength test, permeability test, and toxic leaching test (TCLP), the curing effect of MICP was investigated in the laboratory and the effect of grouting rounds on curing was also analyzed. In addition, the curing mechanism of MICP was studied by means of Fourier transform infrared spectroscopy (FTIR), thermogravimetric analysis (TGA), X-ray diffraction spectroscopy (XRD), and scanning electron microscopy (SEM). The experimental results showed that MICP could induce calcium carbonate precipitation through relatively complex biochemical and physicochemical reactions to achieve the immobilization of heavy metals and sulfides and significantly reduce the impact of tailing sand on the surrounding environment.